Mathematics community portal [electronic resource] - California State University System; MERLOT (Multimedia Educational Resource for Learning and Online Teaching).; MERCED-I (Mindanao Educational Resources for Curricular Enhancement and Development-Initiatives) on OER (Open Educational Resources). (Long Beach, CA MERLOT, 1997)
Quoted from the homepage: Here you will find some of the best mathematics resources hosted on the Internet. We hope you find what you are looking for as you browse through the wealth of resources that will supplement your mathematics teaching and learning. The mathematics editorial board uses the same form for peer reviewing as is used for faculty development. It can be found here: Peer Review Form.
mixed.
online.
Keywords: Electronic information resources; Internet research; Internet in higher education; Open learning; Education, Higher; Electronic books; Algebra -- Open educational resource -- Electronic information resources; Number theory (Mathematics) -- Open educational resource -- Electronic information resources; Analysis (Mathematics) -- Open educational resource -- Electronic information resources; Calculus -- Open educational resource -- Electronic information resources; Mathematics, Developmental -- Open educational resource -- Electronic information resources; Differential equations -- Open educational resource -- Electronic information resources; Discrete mathematics -- Open educational resource -- Electronic information resources; Dynamical systems (Mathematics) -- Open educational resource -- Electronic information resources; Mathematics (Foundations) -- Open educational resource -- Electronic information resources; Mathematics (General) -- Open educational resource -- Electronic information resources; Mathematics (Liberal arts) -- Open educational resource -- Electronic information resources; Geometry -- Open educational resource -- Electronic information resources; Topology (Mathematics) -- Open educational resource -- Electronic information resources; Mathematical modeling -- Open educational resource -- Electronic information resources; Numerical analysis -- Open educational resource -- Electronic information resources; Pre-calculus mathematics -- Open educational resource -- Electronic information resources; Mathematics -- Publishing tools -- Open educational resource -- Electronic information resources